Cardiovascular Diseases Health Literacy among Patients, Health Professionals, and Community-Based Stakeholders in a Predominantly Medically Underserved Rural Environment. Issue 10 (October 2020) - Mamudu, Hadii M.; Wang, Liang; Poole, Amy M.; Blair, Cynthia J.; Littleton, Mary Ann; Gregory, Rob; Frierson, Lynn; Voigt, Carl; Paul, Timir K.
Abstract: Objective: The central Appalachian region of the United States is disproportionately burdened with cardiovascular disease (CVD); however, the level of literacy about CVD among residents has not been well studied. This study aimed to examine the prevalence and factors of CVD health literacy (HL) among a sample of patients/caregivers, providers/professionals, and community stakeholders. Methods: In 2018, data were collected from central Appalachian residents in six states: Kentucky, North Carolina, Ohio, Tennessee, Virginia, and West Virginia. CVD HL status was determined by assessing correct responses to five interrelated questions about basic knowledge of CVD. Multiple logistic regression analyses were used to examine the associations between potential factors and CVD HL status. Results: Of the total respondents (N = 82), <50% correctly answered all 5 CVD HL questions. Multiple logistic regression analyses showed that compared with respondents with advanced college degrees, those with a college degree or less were more likely to have low HL for "typical symptom of CVD, " "physical exercise and CVD, " "blood pressure and CVD, " and "stress and CVD." In addition, compared with respondents younger than 50 years, those 50 years and older were 3.79 times more likely to have low HL for "physical exercise and CVD." Conclusions: These results suggest the incorporation of CVD HL into CVD care and that educational attainments should be part of CVD policies and programs in the region. Abstract : This study examined cardiovascular disease health literacy among a sample of health-related stakeholders in rural central Appalachia using data collected in 2018 from central Appalachian residents in Kentucky, North Carolina, Ohio, Tennessee, Virginia, and West Virginia.